2020
DOI: 10.1039/d0nr03724a
|View full text |Cite
|
Sign up to set email alerts
|

A 2D-SnSe film with ferroelectricity and its bio-realistic synapse application

Abstract: Catering to the general trend of artificial intelligence development, simulating human’s learning and thinking behavior have become the research focus. Second-order memristors, which is more analogous to biologic synapses, are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…[108][109][110][111] In other devices, ferroelectric materials are used as a tunneling barrier in junction devices. [72][73][74] In the beginning, conventional semiconductor channels were replaced by 2D materials, such as graphene and TMDs, in 2D-material-based non-volatile FeRAM, by still using conventional ferroelectric materials such as Pb[Zr x Ti 1−x ]O 3 (PZT) and polyvinylidene fluoride (PVDF). For instance, Chen et al reported a FeRAM device with a channel of graphene and a dielectric of PVDF (Figure 7a), in which the type and density of charge carriers in the channel were tuned by switching the polarization direction of the ferroelectric dielectric (Figure 7b).…”
Section: Ferroelectric Synaptic Devicementioning
confidence: 99%
See 2 more Smart Citations
“…[108][109][110][111] In other devices, ferroelectric materials are used as a tunneling barrier in junction devices. [72][73][74] In the beginning, conventional semiconductor channels were replaced by 2D materials, such as graphene and TMDs, in 2D-material-based non-volatile FeRAM, by still using conventional ferroelectric materials such as Pb[Zr x Ti 1−x ]O 3 (PZT) and polyvinylidene fluoride (PVDF). For instance, Chen et al reported a FeRAM device with a channel of graphene and a dielectric of PVDF (Figure 7a), in which the type and density of charge carriers in the channel were tuned by switching the polarization direction of the ferroelectric dielectric (Figure 7b).…”
Section: Ferroelectric Synaptic Devicementioning
confidence: 99%
“…In addition, the SnSe FeRAM sandwiched by Au and Nb-doped SrTiO 3 shows the bio-synaptic functions of STDP, STP, and LTP due to the gradual ferroelectric polarization switching with high reliability (Figure 7f,g). [74]…”
Section: Ferroelectric Synaptic Devicementioning
confidence: 99%
See 1 more Smart Citation
“…They further showed that stable ferroelectricity could be achieved in both bulk and thin-layer In 2 Se 3 . More recently, another two Tin-based 2D materials, including SnSe and SnS have been experimentally examined to be ferroelectrics by Wang et al and Kwon et al, respectively [40,41]. By using PFM, the SnSe shows out-of-plane polarization behavior, while SnS shows the in-plane polarization behavior with a relatively large remnant polarization (P r ) of 2P r ∼ 40 μC cm −2 .…”
Section: Memory Technologies For Neuromorphic Computingmentioning
confidence: 99%
“…Additionally, they can also be integrated into transistor-type devices with heterostructures to realize synaptic behaviors. More recently, a considerable number of 2D materials (such as WTe 2 , d1T-MoTe 2 , SnTe, CuInP 2 S 6 (CIPS), BA 2 PbCl 4 , α-In 2 Se 3 , β -In 2 Se 3 , 2H α-In 2 Se 3 , SnSe, and SnS) are found to possess ferroelectricity property [32][33][34][35][36][37][38][39][40][41]. Besides, other non-ferroelectric 2D materials can also be easily converted into stable ferroelectric polarization materials by various external factors such as doping, strain engineering, surface modification, and defect engineering [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%